Experience, Problems and Prospects of Practical Implementation of the Concept “Open Government” of the Russian Federation - D. Yu. Desyatnichenko (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
The author’s hypothesis investigated in this article is connected with the statement about the imbalance in the practical implementation of the principles and priorities of the concept of open government in Russia and the need to study the institutional causes of this imbalance. The purpose of the study is to develop conceptual proposals, the implementation of which will help to smooth out and eliminate the imbalances noted above in development. The article on the one hand, notes the clear achievements in solving many technical and technological problems that have recently hampered the formation of e — government, edemocracy, open government. These include only a partial solution at the state level of the problem of functioning of a convenient and legally signifcant system of identifcation of citizens in the electronic environment, the rating of the functioning of the elements of the electronic democracy and the lack of real interest of citizens to participate in decision-making by public authorities, often narrowing in practice the principles of the concept of “Open Government” to the task of ensuring the openness of data. The identified successes and problems in the formation and development of open government elements allow the authors to offer and justify their vision of promising directions for the practical implementation of the concept of “Open Government” in the Russian Federation. Among them: the need of developing and implementing mechanisms to ensure the mandatory participation of a significant number of the country’s citizens in the public discussion of issues directly affecting their interests, their mandatory direct impact on the adoption of socially significant decisions; the expansion of the use of crowdsourcing as an effective, economic and socially effective tool for involving citizens in socially aware decision-making.